2003
DOI: 10.1002/adem.200300377
|View full text |Cite
|
Sign up to set email alerts
|

Recrystallization and Texture in a Ferritic Stainless Steel: an EBSD Study

Abstract: tron diffraction pattern stems from a significantly smaller volume than in the SEM. Additionally, dislocations are visible with the TEM and so localization of subgrains or cell structures is much easier.A TEM image of c-fibre orientations is shown in Figure 7. Subgrain structures are visible here too. However, in this case, the subgrains have a longitudinal shape and are separated by much sharper boundaries. The misorientations between neighboring subgrains are significantly higher as compared to the a-fibre s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 14 publications
(11 reference statements)
1
26
0
Order By: Relevance
“…[13,14] Various explanations have been forwarded to aid in explaining this phenomenon, most being based on the inhomogeneity of the cold-rolled microstructure. [7,8,10,12,[15][16][17][18][19] It is generally agreed that the slow approach to final recrystallization is attributable to the low stored energy and rapid recovery in deformed grains with orientations near {001}Ͻ110Ͼ. [11] Thus, while new grains may form and grow in grains with other orientations, it is observed that deformed grains with near {001}Ͻ110Ͼ orientations are the last to be removed from the microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…[13,14] Various explanations have been forwarded to aid in explaining this phenomenon, most being based on the inhomogeneity of the cold-rolled microstructure. [7,8,10,12,[15][16][17][18][19] It is generally agreed that the slow approach to final recrystallization is attributable to the low stored energy and rapid recovery in deformed grains with orientations near {001}Ͻ110Ͼ. [11] Thus, while new grains may form and grow in grains with other orientations, it is observed that deformed grains with near {001}Ͻ110Ͼ orientations are the last to be removed from the microstructure.…”
Section: Introductionmentioning
confidence: 99%
“…4(c) and 4(f), which could lead to a reduction in rvalue. 7,12,[16][17][18][19][20] However, the {001}͗110͘ component, which is deleterious to r-value, was not completely removed. It can be seen that the densities of the recrystallization texture in cold rolled and annealed sheet of equi-axed bar was a bit greater than those of the columnar bar.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 10 shows the EBSD characterization of the cold rolled sheet of equi-axed cast strip after annealing at 860°C for 10 s. It can be seen that the cold rolled structure consisted of alternative bands of a and g-fiber deformed grains. During cold rolling, it is believed that crystals along initial grain boundaries rotate preferentially to ͗111͘//ND, accompanied by a remarkable increase of misorientation 17) and dislocation density. 30) In this work, similar observation has been obtained, as shown in Fig.…”
Section: Texture Developments In Columnar and Equiaxed Cast Stripsmentioning
confidence: 99%
“…Failures in ferritic stainless steel conformation are known to be related to problems of structural homogeneity caused by the remaining primary solidification structure in the final product [1][2][3][4]. However, recent investigations have revealed that such failures could also be due to chemical segregation [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…It is also necessary to establish the deformation mechanisms of this 3 To whom any correspondence should be addressed. In this study, four AISI 430 (EN 1.4016) steel samples, of different composition, were subjected to uni-and bi-axial tension deformation.…”
Section: Introductionmentioning
confidence: 99%